Rethinking EMI Multidisciplinary Perspectives from Chinese-Speaking Regions - Su, Lily I-Wen; Cheung, Hintat; Wu, Jessica R. W. (Routledge Studies in English-Medium Instruction, 2021)
Due to the competitive edge it confers on students, educational institutions, and non-English speaking nations in a globalized economy, English as a medium of instruction (EMI) has been gaining popularity in tertiary education in non-native English-speaking (NNES) countries. Institute-wide EMI implementation has often been imposed by top-down decisions, in combination with the optimistic view that the horse should always be placed before the cart. However, emerging evidence suggests that the delivery of such programs to NNES students has led to new pedagogical challenges and learning problems that go beyond the scope of language learning and teaching and deserve immediate attention. For example, how would an instructor respond to situations in which students' learning of content is compromised by their limited language proficiency? This book draws on the current practice of EMI in diverse disciplines and university settings and examines how these new pedagogical and learning issues can be addressed. The discussion also involves a reflection on the essence of EMI in relation to the use of the first language (L1) as the medium of instruction in tertiary education. In addition, the book includes discussion about how to ensure and maintain the quality of EMI programs and assess the readiness of stakeholders for such programs, which include administrators, teachers, and students. The discussion is led by exemplars in Hong Kong and Taiwan, where the majority of students are native Chinese speakers, in the hope of developing critical perspectives and practical guidelines as references for EMI in other NNES settings.